2001
DOI: 10.1016/s0014-5793(01)02960-x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin gene expression is inhibited by β‐adrenergic stimulation via protein kinase A in 3T3‐L1 adipocytes

Abstract: Recently, it has been shown that the fat-derived factor adiponectin is downregulated in insulin resistance and obesity and that replenishment of this adipocytokine reverses insulin resistance in mice. Growing evidence, on the other hand, suggests that raised levels of catecholamines due to increased activity of the sympathetic nervous system are an integral part in the development of insulin resistance. To clarify whether catecholamines might exert their insulin resistance-inducing effects at least partly via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
161
2
14

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(193 citation statements)
references
References 38 publications
14
161
2
14
Order By: Relevance
“…Interestingly, a recent paper [33] shows a significant negative relationship between a sympathetic predominance at the heart level and circulating adiponectin levels. Adiponectin secretion is submitted to an inhibitory control by the adrenergic system [34]. This result, therefore, suggests that an increased sympathetic cardiac activity parallels a sympathetic predominance in the adipose tissue.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, a recent paper [33] shows a significant negative relationship between a sympathetic predominance at the heart level and circulating adiponectin levels. Adiponectin secretion is submitted to an inhibitory control by the adrenergic system [34]. This result, therefore, suggests that an increased sympathetic cardiac activity parallels a sympathetic predominance in the adipose tissue.…”
Section: Discussionmentioning
confidence: 91%
“…Some other studies have reported similar disassociation between adiponectin levels and insulin resistance 28,29 and the relationship between adiponectin and IR is probably not one of the direct cause and effect in all patients. It is possible that their inverse relationship may be mediated not only by insulin levels but also by other hormones such as catecholamines or androgens, [30][31][32] as well as by pro-inflammatory cytokines, 33,34 and some medications. 31,35 Our results also depict the prominent role that adipose tissue plays in both insulin resistance and the clinical expression of the metabolic syndrome (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Various hormones inducing insulin resistance down-regulate adiponectin expression. Thus, β-adrenergic activation inhibits adiponectin mRNA expression by up to 75% in differentiated 3T3-L1 cells in vitro (Table 1) [97]. Similarly, adiponectin mRNA and protein synthesis are down-regulated in human adipocytes in vitro by β-adrenoceptor agonists with β3-agonists having the most potent effects [98].…”
Section: Adiponectinmentioning
confidence: 97%